The Effect of Customer Experience on Fast Fashion Actual Product Repurchase (Journal of Business and Management, 2022)
From year to year, fast-fashion retail is increasingly popular in Indonesia, such as H&M and ZARA. As fast fashion is constantly being updated, new things enter the store and are quickly replaced by the next collection, so some consumers may not get the chance to see the product twice as they are captivated by new clothes every time they visit the store. These two fast-fashion brands offer similar products but with different experiences. In this case, the in-store customer experience is one part of the marketing strategy that must be considered to maintain the continuity of the brand, besides that an attractive in-store customer experience can also attract consumers to make actual product repurchases. The in-store customer experience component includes cognitive experience, affective experience, social experience, and physical experience. These components help shape and build a more engaging customer experience for consumers. This research was conducted through a qualitative approach with semi-structured interviews and a quantitative approach with an online survey of fast-fashion product users who have purchased products at H&M and ZARA at least once in the last six months. Questionnaires were distributed through online surveys in Greater Jakarta and Bandung to 272 respondents who had bought fast fashion products, especially at H&M and ZARA. This study uses the PLS-SEM method to analyze the collected data. The results of this study show that there is a gap between two largest fast fashion retail in the world which is H&M and ZARA, this study also illustrate that cognitive experience has a positive impact on post purchase experience, social experience has a positive impact on brand experience and service provider experience also post purchase experience, physical experience has a positive impact on service provider experience, brand experience and service provider experience also post purchase experience has a positive impact on the actual product repurchase.Keywords: Cognitive Experience, Affective Experience, Social Experience, Physical Experience, Customer Experience, Actual Product Repurchase, Fast-fashion